Determination of The Levels of Lead (Pb), Total Microbes and E coli on Blood Cockles Marketed in the Sidoarjo Regency - Retyoadhi, Alfa Yusuf; Susanto, Tri; Martati, Erryana (Jurnal Teknologi Pertanian, 2005)
Blood cockles (Anadara granosa Linn) has filter feeder properties, therefore they may accumulate contaminants such as heavy metals and microorganisms in their flesh. The purpose of this study is to determine the levels of Pb, total microorganisms and total E. Coli of fresh blood cockles marketed in Sidoarjo regency. The samples were randomly taken from the Cemandi Fishery Auction in the district of  Sedati, Sidoarjo and Sidoarjo Fishery Market. In each location,  the samples was randomly obtained from three different places. The levels of moisture, Pb, total microorganisms and total E. coli of the samples were then determined. The results showed that the Pb level of fresh blood cockles in Sidoarjo was 0,0153-0,0523 ppm (at moisture content 75 %). Total microorganisms and E. coli of fresh blood cockles were 3,03x103-20x103 cfu/g and 0,00-20 cfu/100g, respectively. The Pb and total microorganism levels were lower than those of the Indonesia Quality Standard of Agriculture Product and FDA standards. However, from  the seven samples, three of which contained total E Coli exceeding the one of the Indonesia Quality Standard of Agriculture Product and FDA standards. Therefore, it is advised to cooked the blood cockles properly before consumption.   Keyword : fresh blood cockles, Pb, total microorganism, E coli.